The Incidence and Management of Dural Tears and Cerebrospinal Fluid Leakage during Corrective Osteotomy for Ankylosing Spondylitis with Kyphotic Deformity - Jo, Dae-Jean (J Korean Neurosurg Soc, 2015)
OBJECTIVE: To present the incidence and management of dural tears and cerebrospinal fluid leakage during corrective osteotomy [Pedicle Subtraction Osteotomy (PSO) or Smith-Petersen Osteotomy (SPO)] for ankylosing spondylitis with kyphotic deformity. METHODS: A retrospective study was performed for ankylosing spondylitis patients with fixed sagittal imbalance, who had undergone corrective osteotomy (PSO or SPO) at lumbar level. 87 patients were included in this study. 55 patients underwent PSO, 32 patients underwent SPO. The mean age of the patients at the time of surgery was 41.7 years (21-70 years). Of the 87 patients, 15 patients had intraoperative dural tears. RESULTS: The overall incidence of dural tears was 17.2%. The incidence of dural tears during PSO was 20.0%, SPO was 12.5%. There was significant difference in the incidence of dural tears based on surgical procedures (PSO vs. SPO) (p<0.05). The dural tears ranged in size from 12 to 221 mm(2). A nine of 15 patients had the relatively small dural tears, underwent direct repair via watertight closure. The remaining 6 patients had the large dural tears, consequently direct repair was impossible. The large dural tears were repaired with an on-lay graft of muscle, fascia or fat harvested from the adjacent operation site. All patients had a successful repair with no patient requiring reoperation for the cerebrospinal fluid leak. CONCLUSION: The overall incidence of dural tears during PSO or SPO for ankylosing spondylitis with kyphotic deformity was 17.2%. The risk factor of dural tears was complexity of surgery. All dural tears were repaired primarily using direct suture, muscle, fascia or fat graft.